Demographic, HIV risk behavior, and health status characteristics of "crack" cocaine injectors compared to other injection drug users in three New England cities. - Buchanan, David; Tooze, Janet A; Shaw, Susan; Kinzly, Mark; Heimer, Robert; Singer, Merrill (Drug and alcohol dependence, 2006)
To compare demographic, HIV risk behaviors, and health status characteristics of injection drug users (IDUs) who have injected "crack" cocaine with IDUs who have not.
Keywords: Adult; Catchment Area (Health); Cocaine-Related Disorders; Crack Cocaine; Cross-Sectional Studies; Demography; Female; Health Status; HIV Seropositivity; Humans; Male; Massachusetts; Prevalence; Questionnaires; Risk-Taking; Sexual Behavior; Substance Abuse, Intravenous